The crypto effect on cross border transfers and future trends of cryptocurrencies - Burak Uyduran (Financial Internet Quarterly, 2020)
This paper presents a theoretical and empirical outlook on different aspects of various cryptocurrencies, blockchain technology including the evolution of digital tokens and how they widely affect the financial markets, organizations, banks, governments via analyzing the characteristics and current history of cryptocurrencies alongside with blockchain technology. The choice of this topic was motivated by the fact that the virtual money concept and blockchain technology are utterly new phenomena. This new technology is completely decentralized making the subject worthy of scientific research.The paper solely focuses on analyzing how cryptocurrencies currently affect the financial markets and the future trends of these virtual tokens in the global economy. The study is keen to further examine the impact of Bitcoin and other cryptocurrencies on international fund transfers. Literature review and case study with up-to-date data has been included in the analysis. The following results have been obtained: cryptocurrencies offer a wide range of features such as faster, cheaper and more secure cross-border money transfers that can also provide anonymity. Most crypto tokens are highly volatile due to their nature and various other factors. Cryptocurrencies could provide more beneficial options for users on cross border transfers compared to traditional methods of fund transfers. Cryptocurrencies might have the potential to replace paper money and gain mainstream recognition throughout the world. The study sheds light onto current and future trends of cryptocurrencies and blockchain. It is outlined for the crypto, financial, economic field.
Keywords: G10; G15; G20; 330; cryptocurrency; blockchain; bitcoin